33.0k views
4 votes
Which expression is equivalent to −3x + 5.1? A) −3(x + 1.7) B) −3(x − 1.7) C) 3(x + 1.7) D) 3(x − 1.7)

User Channy
by
5.0k points

2 Answers

5 votes

Answer:

B) −3(x − 1.7)

Explanation:

−3(x−1.7)

=(−3)(x+−1.7)

=(−3)(x)+(−3)(−1.7)

=−3x+5.1

User Dinero
by
5.4k points
2 votes

Answer:

B) −3(x − 1.7)

Explanation:

Apply the distributive property of multiplication over addition or over subtraction in each case, which is a(b + c) = ab + ac or a(b - c) = ab - ac.

A) −3(x + 1.7) = = -3(x) + (-3)(1.7) = -3x - 5.1

B) −3(x − 1.7) = -3(x) - (-3)(1.7) = -3x + 5.1 <------------ answer

C) 3(x + 1.7) = 3(x) + 3(1.7) = 3x + 5.1

D) 3(x − 1.7) = 3(x) - 3(1.7) = 3x - 5.1

User Shyam Sundar Shah
by
5.1k points